The Effect of Circuit Training and Fartlek Training on Increasing Vo2 Max in Taekwondo Athletes (Based on Gender) - Kay Radjasa Muhammad; Endang Rini Sukamti (Universitas Negeri Semarang, 2026)
This study aims to determine: (1) There is a significant effect of circuit training and fartlek training on increasing VO2 Max of male and female Taekwondo athletes of POPB DKI Jakarta 2023. (2) There is a significant difference in increasing VO2 Max of male and female Taekwondo athletes of POPB DKI Jakarta 2023. (3) There is a relationship between circuit training and fartlek training based on gender on increasing VO2 Max of Taekwondo athletes of POPB DKI Jakarta 2023. This type of research is an experiment with a “Two Group Pretest-Posttest Design” design. The population in this study were 28 athletes of POPB DKI Jakarta 2023. Sampling in this study was carried out using purposive sampling of 28 athletes. The instrument for measuring VO2 Max was a multistage fitness test. The data analysis technique used was the Two-Way ANOVA Test. The results of the study showed that: (1) Circuit training and fartlek training did not have a significantly different effect in terms of increasing VO2 Max in taekwondo athletes, but fartlek was superior in increasing VO2 Max. (2) The difference between male and female gender was significant in its effect on increasing VO2 Max in taekwondo athletes. (3) The circuit training method and fartlek training did not have a gender interaction in increasing VO2 Max in taekwondo athletes. Fartlek training was better than circuit training in increasing VO2 Max in taekwondo athletes at POPB DKI JAKARTA 2023.